High-speed vessel moving along the edge of ice field - Marleaux, Patrick; Khabakhpasheva, Tatiana; Abdel-Maksoud, Moustafa; Korobkin, Alexander; Maki, Kevin (Istituto di Ingegneria del Mare, 2022)
A domain decomposition approach is proposed to study the problem of a high-speed vessel which moves in close proximity to the edge of an ice field. A two-dimensional boundary element method which incorporates fully non-linear free surface conditions shall be used in combination with 2D+t theory to model the flow in the open water region. Theory of linear hydro-elasticity shall be used in the ice covered region with the ice modelled as semi-infinite, thin and elastic plate of constant thickness. A non-local boundary is specified on a fictitious boundary between both regions to account for interaction effects. US Office of Naval Research